2020
DOI: 10.1111/ceo.13728
|View full text |Cite
|
Sign up to set email alerts
|

Fasting plasma glucose variability is an independent risk factor for diabetic retinopathy and diabetic macular oedema in type 2 diabetes: An 8‐year prospective cohort study

Abstract: Importance: Long-term stability in plasma glucose may affect the development of diabetic retinopathy (DR) and diabetic macular oedema (DMO).Background: To investigate the associations between glycaemic variability and the development of DR and DMO in type 2 diabetes (T2D).Design: An 8-year prospective cohort study. Participants: 2005 patients with T2D.Methods: DR and DMO were detected with non-mydriatic fundus photography. Main outcome measures:The visit-to-visit variability of fasting glucose or HbA1c was cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…2017) and is similar to the risk pattern for developing DME independently of cataract surgery (Hove et al. 2006; Bek 2020b; Hsiah & Hsiah 2020).…”
Section: Discussionsupporting
confidence: 67%
“…2017) and is similar to the risk pattern for developing DME independently of cataract surgery (Hove et al. 2006; Bek 2020b; Hsiah & Hsiah 2020).…”
Section: Discussionsupporting
confidence: 67%
“…FBG was positively correlated with ORT of the mid-peripheral regions and negatively correlated with VD of part regions in the DCP layer. A number of reports suggested that FBG is an independent risk factor for the occurrence of DR ( 34 ). Elevated FBG in diabetic patients increases hemoglobin glycosylation and increased glycosylation of hemoglobin increases its affinity for oxygen, therefore, preventing its release at the tissue inducing hypoxia and oxidative stress (OS), which further leads to a decrease in VD ( 35 ).…”
Section: Discussionmentioning
confidence: 99%